Penggunaan media pembelajaran balok Iqro’ Braille untuk meningkatkan kemampuan membaca Iqro’ anak dengan hambatan penglihatan - Ardhia Pramesti Adhi; Ratih Listyaningtyas; Sistriadini Alamsyah Sidik (UNIK (Jurnal Ilmiah Pendidikan Luar Biasa), 2020)
This research is motivated by the problems that researchers found in SKh YKDW 03 Tangerang in children with visual impairment grade 7th in iqro' braille learning. This research aims to determine whether the use of “balok iqro’ braille” learning media has a significant influence in improving the ability to read iqro of children with visual impairment. This type of research is an experimental study with single subject research. Data collection techniques used are observation, documentation, and instruments. Observations were made to observe the ability to read iqro' research subject. Documentation is used as evidence that will strengthen the results of research and instruments created to collect data regarding the ability to read iqro' research subject. The subjects involved in this study were one child. The results obtained by the subject seen from changes in the level of data in the analysis between conditions in the intervention phase to the baseline-1 (A1) phase increased by 50 points due to the treatment. Whereas in the baseline-2 (A2) phase the intervention experienced an increase of (-15) points. Although in the baseline-2 (A2) phase the data obtained is lower than the intervention phase, but the data obtained is higher than the data in the baseline-1 (A1) phase. In addition, overlap data in the intervention phase (B) to baseline-1 (A1) and the baseline-2 (A2) to intervention (B) phase have an overlap percentage of 0%. Thus the results of this study can answer the hypothesis that by using “balok iqro’ braille” the ability to read iqro’ of children with visual impairment grade 7th can be improved.